Diseño y construcción de un banco de pruebas termodinámico con un sistema intercambiador de calor de tubos y coraza (2021)
This document describes the design and construction of a test bench with a shell and tube heat exchanger so that its operation is clearly evidenced as well as the measurements of the variables involved in the process, so that its set is a didactic element in the learning of matters related to heat transfer. Additionally, it contains laboratory guides in which the student can carry out practices that will facilitate the understanding of the heat exchange method that this type of exchangers present, in a practical, didactic, technical and friendly way. For the design and subsequent manufacture, AutoCAD software was used, according to the design requirements and the designated space in the laboratory of thermal and hydraulic machines of the university. We propose this endeavor as a result of the current absence of a test bench with this type of exchangers in the south headquarters of the university and its notorious presence in the industry